A toy model for a baby universe inside a black hole - Cosimo Bambi; Daniele Malafarina; Ahmadjon Abdujabbarov; Hrishikesh Chakrabarty; Hrishikesh Chakrabarty (Springer, 2020)
Dynamical toy model for an expanding universe inside a black hole via matching to FRW after a quantum-gravity-dominated transition; matching on a space-like hypersurface halting collapse.
Keywords: type of access: open access; quantum gravity; baby universe; black hole; toy model; toy model